Small and medium industries in Terengganu and their contribution to the state economy / Norudin Mansor ... [et al.] - Mansor, Norudin; Abu Bakar, Nordin; Wan Mahmood, Wan Mansor; Jaafar, A. Aziz (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
The economic growth of the country and the existence of external investors added to the strength of the world economic climate, help to create more avenues for the local investors towards improving the SMI sectors. Since 1 987 the total investments in SMIs had increased tremendously from RM61.7 million to RM629 million. In 1991 alone, SMIs in Malaysia expanded at the rate of 89.5%. However, Malaysia which had been considered as a developing country is still far behind when compared to newly industrialized countries such as South Korea, Taiwan, Hong Kong and Singapore.